Convergence at last? Evidence from Transition Countries - Sašo Polanec (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 2004)
In this paper, we test the neoclassical growth model and its main prediction of conditional convergence of productivity for a sample of transition countries over the period 1990-2002. We split the sample into three periods: 1990-1994, 1994-1998 and 1998-2002 and confirm the convergence hypothesis only for the last period of transition, while in the early transition, factors specific to the transition process dominated productivity growth. We confirm past findings of importance of the process of liberalization and initial conditions for explaining differences in productivity growth. In the period 1998-2002, transition specific factors play no negative role, while in the period 1994-1998 their role is substantially reduced. These results, however, should not yet be intepreted as a sign of a pfirmenent return to convergence in transition countries as they could be caused by differences in transition cycle.
Keywords: O40; O41; O51; O52; O53; 330; convergence; neoclassical growth; regional growth; Wirtschaftswachstum; Entwicklungskonvergenz; Übergangswirtschaft; Deregulierung; Neoklassik; Osteuropa